Students’ Learning Strategies Based on Their VAK Learning Style - Novi Dwi Yuliani; Lailatun Najmiah (Intensive Journal, 2019)
Learning styles have huge contributions in developing the efficiency in education. The concept of learning styles has been explored by many experts in various background of study. Fleming (2001) defines learning style as an individual’s characteristics and preferred ways of gathering, organizing, and thinking about information. This study aims to identify the students’ learning styles according to the classifications of learning styles and how their learning strategies. VAK questionnaire was utilized in this study to know the students’ preferred learning styles. Interview was also conducted in collecting some additional information regarding the students’ learning. 21 adult EFL learners majoring in English education of postgraduate Program of Universitas Ahmad Dahlan were involved as a research sample. From the interview conducted to three participants as representatives of each learning styles it was discovered that each learning has its own learning strategy which is different from one another. One respondent as a visual learner argued that she felt happy if the lecturer provides visual-demonstration in class such as movies, videos, and PowerPoint presentation. Another respondent as an auditory learner preferred to learn by listening and writing down important information that she have learnt. The other respondent as a kinaesthetic learner would find easy to understand and remember well if she was involved practice.